A Bird's-Eye View: How Birds Select Habitat - Mark E. Hostetler (EDIS, 2003)
This document is Fact sheet WEC-163, one of a series of the Department of Wildlife Ecology and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published January 2003.